"If I Don't Do It, Somebody Else Will": Covert Neoliberal Policy Discourses in the Decision‐Making Processes of an Intensive English Program. Issue 4 (9th January 2020) - Litzenberg, Jason
Abstract : Intensive English programs (IEPs) have traditionally been central actors in promoting teacher professional development, curricular innovations, and applied linguistics and second language acquisition research. Yet at the same time, the programs are also central actors in neoliberal linguistic commodification. This article demonstrates how neoliberalism influences the covert policy discourses of the decision‐making processes of an IEP. Using an analytic autoethnographic approach to present an interwoven series of narratives and analyses, the article argues that IEP administrators, faculty, and staff are limited in how they can contest their complicity at propelling a neoliberal institution profiting from language education. The article also demonstrates how neoliberal positioning took precedence over pedagogical discourses in certain decision‐making processes and impeded the experimentation and exercise of an innovative curriculum, and it suggests ways that the neoliberal orientation of IEPs currently impacts and eventually may alter the nature of MA TESOL. The issues presented here not only reflect the experiences and concerns of professionals in English language teaching, but they are also timely in that IEPs have been largely underrepresented in the expanding discussions of the relationship between applied linguistics, its subfields, and neoliberalism.